2020
DOI: 10.1177/0363546520940715
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgical Repair of Medial Meniscus Posterior Root Tear Minimizes the Progression of Meniscal Extrusion: 2-Year Follow-up of Clinical and Radiographic Parameters After Arthroscopic Transtibial Pull-out Repair

Abstract: Background: Conflicting results have been reported concerning the progression of medial meniscal extrusion (MME) after arthroscopic transtibial pull-out repair of medial meniscus posterior root tear (MMRT), and no study has evaluated the relevant factors affecting the progression of MME. Purpose: To (1) evaluate the subjective and objective surgical outcomes of arthroscopic transtibial pull-out repair of MMRT and (2) identify relevant factors affecting the progression of MME after surgery. Study Design: Case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 41 publications
(72 reference statements)
1
64
0
Order By: Relevance
“…A flow chart regarding the screening of the articles is shown in Figure 1; 22 studies were selected for fulltext review, all of which satisfied our inclusion and exclusion criteria; 4 studies included partial meniscectomy groups, 2 studies included conservative groups, all studies included repair groups. In the 22 studies, 14 were Level III evidence, 5,[9][10][11][12][13][17][18][19][20]22,[27][28][29] 8 were Level IV evidence. [6][7][8]21,24,[30][31][32] Among the Level III evidence comparative studies, three compared partial meniscectomy with pull-out suture repair 9,13,27 and one compared conservative treatment with pull-out suture repair, 28 one compared meniscectomy, repair and conservative treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A flow chart regarding the screening of the articles is shown in Figure 1; 22 studies were selected for fulltext review, all of which satisfied our inclusion and exclusion criteria; 4 studies included partial meniscectomy groups, 2 studies included conservative groups, all studies included repair groups. In the 22 studies, 14 were Level III evidence, 5,[9][10][11][12][13][17][18][19][20]22,[27][28][29] 8 were Level IV evidence. [6][7][8]21,24,[30][31][32] Among the Level III evidence comparative studies, three compared partial meniscectomy with pull-out suture repair 9,13,27 and one compared conservative treatment with pull-out suture repair, 28 one compared meniscectomy, repair and conservative treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8]21,24,[30][31][32] Among the Level III evidence comparative studies, three compared partial meniscectomy with pull-out suture repair 9,13,27 and one compared conservative treatment with pull-out suture repair, 28 one compared meniscectomy, repair and conservative treatment. 11 The rest of the studies reported subgroup analysis of repair treatment of MMPRTs, 5,10,12,[17][18][19][20]22,29 including different surgical technique 5,10,18,20,22,29 and meniscus extrusion changes after repair of MMPRTs. 12,17,19 Of the Level IV case series studies, eight studies reported the outcomes of repair in MMPRTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the interest in our paper entitled ''Early Surgical Repair of Medial Meniscus Posterior Root Tear Minimizes the Progression of Meniscal Extrusion,'' 8 and are grateful to have the opportunity to receive feedback on our work. Given the clinical significance of medial meniscus posterior root tear (MMRT) and the recent surge in interest in it, there is a need for continued discussion on this topic in order to spur further research and advances in this area.…”
Section: Dear Editormentioning
confidence: 99%
“…We read with interest the recent paper by Moon et al 4 evaluating the clinical outcomes of arthroscopic transtibial pull-out repair of medial meniscus posterior root tear (MMRT) and identifying relevant factors affecting the progression of medial meniscal extrusion (MME). While the overall study is well done, the authors neglected several factors that may play crucial roles in the progress of MME.…”
mentioning
confidence: 99%